2016
DOI: 10.1007/978-3-319-22692-7_1
|View full text |Cite|
|
Sign up to set email alerts
|

Dimeric Sesquiterpenoids

Abstract: It is widely accepted that a large number of proteins that are responsible for cellular function exist as dimers or need to be activated by dimerization before mediating certain signaling pathways. Simultaneously targeting both monomeric moieties of the dimeric proteins has shown potential in the development of various therapeutic agents. As dimeric molecules might be able to act on both moieties of a dimeric protein, dimeric sesquiterpenoids (DSs), which are generated biogenetically from coupling of two sesqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 262 publications
0
17
0
Order By: Relevance
“…Since the first SLD absinthin was isolated from Artemisia absinthium in 1953 3 , more than 160 SLDs have been obtained. To the best of our knowledge, most of the published SLDs have C 30 cores derived from two C 15 sesquiterpenoid units 4 5 6 .…”
mentioning
confidence: 99%
“…Since the first SLD absinthin was isolated from Artemisia absinthium in 1953 3 , more than 160 SLDs have been obtained. To the best of our knowledge, most of the published SLDs have C 30 cores derived from two C 15 sesquiterpenoid units 4 5 6 .…”
mentioning
confidence: 99%
“…This includes polyacetylenes [910] as well as sesquiterpenoids with illudine [11], aromadendrane [12], marasmene [13] and fomannosane [14] type skeletons. Although bovistol could formally be supposed to be a triterpene, it is thought to be derived by a hetero-Diels–Alder reaction of two sesquiterpenes to form a dimeric sesquiterpenoid [15].…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, a variety of sesquiterpenoid dimers with potential in the treatment of liver cancer [ 6‐7 ] and antiinflammatory activities have been isolated from Artemisia species. [ 8‐19 ] Guaiane‐type sesquiterpenoid dimers are the main classes of sesquiterpenoid dimers in this genus, predominantly composed of two alike or unlike monomeric sesquiterpene lactone units through different connecting model. Chemical investigations showed that 77 guaiane‐type sesquiterpenoid dimers had been identified from Artemisia plants in the last 40 years, and most of them were generated via intermolecular Diels–Alder reaction to produce an additional cyclohexene moiety.…”
Section: Background and Originality Contentmentioning
confidence: 99%